First to the last place on Earth! - Stilton, Geronimo; Savino, Francesco, 1986-; Favia, Leonardo (Geronimo Stilton graphic novel, 2016)
Geronimo and his friends go back in time and race the Pirate Cats to be the first to the South Pole.